2012
DOI: 10.1039/c2cp42434g
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the reaction of OH with the trimethylbenzenes – experimental evidence for the formation of adduct isomers

Abstract: The reversible gas-phase addition of OH radicals to the trimethylbenzenes was investigated in pulsed experiments utilizing VUV flash-photolysis resonance-fluorescence of H(2)O in the temperature range of 275-340 K. Triexponential OH decays were observed in the presence of the trimethylbenzenes, indicating the participation of more than one adduct species. Analytical solutions for the system of differential equations with two adduct isomers were derived, and the OH decay curves were evaluated based on this reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(69 citation statements)
references
References 30 publications
5
64
0
Order By: Relevance
“…The k OH of 135-TMB led to a slightly weaker temperature dependence than in previous work of Aschmann et al, 31 but in agreement with the work of Bohn and Zetzsch. 11 However, the k OH of this work are greater by about 25%. Room temperature k OH for 1245-TeMB and PMB are in good agreement with recent relative rate measurements by Aschmann et al 32 at 298 K while for 1234-TeMB and 1235-TeMB no literature data are available.…”
Section: Oh + Aromatics Rate Constantsmentioning
confidence: 95%
See 3 more Smart Citations
“…The k OH of 135-TMB led to a slightly weaker temperature dependence than in previous work of Aschmann et al, 31 but in agreement with the work of Bohn and Zetzsch. 11 However, the k OH of this work are greater by about 25%. Room temperature k OH for 1245-TeMB and PMB are in good agreement with recent relative rate measurements by Aschmann et al 32 at 298 K while for 1234-TeMB and 1235-TeMB no literature data are available.…”
Section: Oh + Aromatics Rate Constantsmentioning
confidence: 95%
“…k L1 = [k À11a + k 31 ] and 4,11,20 but they may be affected by the use of the wrong reaction model. 11 In contrast, the activation energy for the OH-HMB adduct is greater (89 kJ mol À1 ).…”
Section: Model-dependent Fit Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, a study of OH + trimethylbenzenes has also reported evidence for ipso-adduct formation, but this channel was in any case a minor process. 8 Among the various oxidation products arising from the OHinitiated oxidation of monocyclic aromatic compounds, ringretaining species such as benzaldehyde, cresols, as well as highly…”
Section: ■ Introductionmentioning
confidence: 99%